THE EFFECT OF PROFITABILITY ANALYSIS ON COMPANY VALUE WITH GOOD CORPORATE GOVERNANCE AS A MODERATE VARIABLE - Pramesti, Florentina Yuniar; Rita, Maria Rio (International Journal of Social Science and Business, 2021)
This research aims to analyze Rentability to The Company Value with GCG (Good Corporate Governance) as a moderating variable. The rentability variable is measured using the Return on Assets (ROA) value. While the Company's Value is measured by Tobin's Q. GCG as moderation variable is measured by two proxies, namely the Independent Board of Commissioners and the Audit Committee. The samples in this study were 10 state-owned enterprises companies (BUMN) in the finance and insurance sector, which listed on the Indonesia Stock Exchange (IDX) for the period 2016-2020. The technique used in the study was purposive sampling. The results show that Rentability significantly affects the Company's Value.Â  Based on the calculated t value (3,955) > table t (0.677) and the Sig value (0.000) < 0.05. The GCG (Good Corporate Governance) is able to moderate the influence of Rentability on the company value based on the calculated t value (8,096) > t table (0.677), and the Audit Committee based on the calculated t value (8,332) > t table (0.677). Rentability is able to explain the variable variation in the company value based on the R2 value of 28.5% and GCG (Independent Board of Commissioners and Audit Committee) is able to strengthen the relationship between rentability and the company's value to 47.7%.